Measurements of the associated production of a W boson and a charm quark in proton-proton collisions at ?s=8TeV - Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Ero, J.; Del Valle, A. Escalante; Fruhwirth, R. (Springer, 2022)
Measurements of the associated production of a W boson and a charm (c) quark in proton-proton collisions at a centre-of-mass energy of 8 TeV are reported. The analysis uses a data sample corresponding to a total integrated luminosity of 19.7 fb(-1) collected by the CMS detector at the LHC. The Wbosons are identified through their leptonic decays to an electron or a muon, and a neutrino. Charm quark jets are selected using distinctive signatures of charm hadron decays. The product of the cross section and branching fraction sigma(pp -> W + c + X)B(W -> l nu), where l = e or mu, and the cross section ratio sigma(pp -> W+ + (c) over bar + X)/sigma(pp -> W- + c + X) are measured in a fiducial volume and differentially as functions of the pseudorapidity and of the transverse momentum of the lepton from theWboson decay. The results are compared with theoretical predictions. The impact of these measurements on the determination of the strange quark distribution is assessed.